Alternative Values-Based 'Recipes' for Life Satisfaction: German Results with an Australian Replication - Bruce Headey; Gert G. Wagner (Institute of Labor Economics (IZA), 2018)
In most research on Life Satisfaction (LS), it is assumed that the covariates of high and low LS are the same for everyone, or at least everyone in the West. In this paper, analysing data from the German Socio-Economic Panel, with a limited replication based on Australian panel data, we estimate models of alternative 'recipes' for LS. There appear to be at least four distinct 'recipes', which are primarily based on the values of different population sub-sets. These values are: altruistic values, family values, materialistic values and religious values. By a 'recipe' for LS we mean a linked set of values, behavioural choices and domain satisfactions, which appear to be held together by a person's values, and which prove to have substantial effects on LS. Our German and Australian evidence indicates that individuals who follow recipes based on altruistic, family or religious values record above average long term LS, whereas the materialistic values 'recipe' is associated with below average LS.
Keywords: C55; I31; Z13; 330; life satisfaction; alternative recipes; values/life priorities; behavioural choices; domain satisfactions; panel data; SOEP